The Effect of Information Quality on the Internal Operation Effectiveness At Commercial Banks in Jordan: Applied Study - AL-mahasneh, Mohammad (The Arab Journal of Administration, 2020)
This study aims to analyze the effect of the information quality on the Internal operation Effectiveness at Commercial Banks in Jordan. To achieve the objective goals of the study, a questionnaire has been developed and distributed to simple random sample which consists of (333) subjects, (265) questionnaire were retimed and valid to statistical analysis which represent 79.58% of the sample size. The study has reached the following results: There is a significant statistic effect of information quality on the Internal operation Effectiveness, an effect of information content and time on the social interaction, and an effect of the information content on the Internal operation Effectiveness at commercial Banks in Jordan. The study recommended that the bank’s management should direct the banks to pay more attention for the process and time of offering information, through developing and modernizing the services, especially innovation process.